Student investors place in national competitions - Archive, FSN::::::::: (2013)
Nineteen students from Fresno State's Craig School of Business' Student Investment Fund Class (FIN 129) placed at two national conferences in April, based on the performance of their $1.41 million dollar investment portfolio.